2008
DOI: 10.1143/jjap.47.5944
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Layer Detection of Rotating Multilayered Optical Memory

Abstract: We fabricated disc-type multilayered media with several refractive indices of pressure-sensitive adhesives for dynamic layer detection. We modified a commercially available disc tester in order to obtain two types of signal; one is the confocal signal and the other is the astigmatic signal. The confocal signal provides sufficient signal to detect recording layers, but the astigmatic signal is not useful because the reflected signals from the internal layers are too small. The confocal detection also provides s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A promising approach to green archival storage is the use of optical disks due to their large capacity, low running cost, and longevity. While their capacity can be readily expanded by increasing the number of recording layers, [1][2][3][4][5][6][7][8][9][10] the groove structure needed for tracking control increase the disk fabrication cost. 11) For example, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A promising approach to green archival storage is the use of optical disks due to their large capacity, low running cost, and longevity. While their capacity can be readily expanded by increasing the number of recording layers, [1][2][3][4][5][6][7][8][9][10] the groove structure needed for tracking control increase the disk fabrication cost. 11) For example, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Reflecting such a situation, multilayer discs holding more than 10 layers have been widely studied in the laboratory stage. [3][4][5][6][7][8][9][10][11][12][13] Ogasawara et al reported 16and 20-layer read-only discs 5) and 16-layer write-once discs 10) with the same density as BD or BDXLÔ. In ref.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a multilayered optical memory using a multilayered medium that was fabricated with a laminating process. [13][14][15][16] Because the medium was a stack of films, the thickness of each layer of the multilayered optical memory is uniform.…”
Section: Introductionmentioning
confidence: 99%